Chinese as a foreign language project-based learning using TikTok: students’ perceptions on learning process and online discourse - Leow, Min Hui; Hassan, Norhaslinda (Universiti Teknologi Mara Cawangan Pulau Pinang, 2026)
Chinese as a Foreign Language (CFL) learners often experience anxiety, largely due to limited authentic communication opportunities and negative pedagogical practices, which hinder their confidence, performance, and achievement. Hence, this study investigates the perceived impact of TikTok-integrated project-based learning (PBL) on CFL learners, to explore students’ perceptions of the online learning process and online discourse. A qualitative case study design was used to explore the perspectives of 16 undergraduates on their competencies, experiences, and sociocultural interactions. The study design incorporated John Dewey’s theories of experientialism, constructivism, and constructionism, along with Merrill Swain’s Output Hypothesis and Vygotsky’s Sociocultural Theory of Mind. The findings revealed that while students initially faced challenges with metalinguistic elements, implementing PBL through TikTok enhanced their engagement and confidence, and supported perceived language development. The platform facilitated collaborative language practice, creative expression, and constructive feedback. However, challenges in creative and critical thinking were identified, suggesting a need for further support. The study underscores the potential of TikTok as a valuable tool for innovative CFL teaching, emphasising the importance of addressing students’ specific needs and providing additional guidance on project accomplishment.